SYNTHESIS OF NEW BIOLOGICALLY ACTIVE PYRIMIDINECARBOXAMIDES CLASS SUBSTANCE WITH HIGH ANALGESIC ACTIVITY - Buzmakova, N.A. (Perm Federal Research Centre Journal, 2015)
The new pyrimidine derivatives were synthesized by the modified three-component Biginelli reaction. During the screening study of their biological activities the new substance of pyrimidine-5- carboxamides with high analgesic activity and low toxicity were selected.